PERBEDAAN TEKANAN DARAH DENGAN PENGGUNAAN SUMBAT TELINGA (EAR PLUG) PADA PEKERJA PANDE ALUMUNIUM DI DESA KEMBANG KUNING KABUPATEN BOYOLALI - Listianto, Kabul; , Tarwaka, PGDip Sc, M.Erg; , Sri Darnoto S.KM M.PH (2015)
Noise is one of the important problems in the home industry because it can lead to blood pressure workers. In general, high-pitched noise is very disturbing even more disjointed or which come suddenly and unexpectedly can cause physiological reactions such as changes in blood pressure (± 10 mmHg), increased pulse rate, basal metabolism, sleep disorders, etc. Aluminum workers labor at Kembang Kuning Village, Boyolali District, have a risk of changes in blood pressure. This research is a experimental studies research with one group pretest-postest design approach. The study population of 150 male workers with quota sampling, the number of samples studied 40 respondents. Processing techniques and data analysis conducted by Wilcoxon statistical test using a computer program in the faculty of health sciences laboratories. The results of blood pressure based on the characteristics of the respondents at the time did not using ear plugs are: normal 7 workers, as many as 6 workers with mild hypertension, hypertension were 25 workers, while severe hypertension 2 workers. Blood pressure based on the characteristics of the respondents while using the ear plug is: normal 19 people, 15 people with mild hypertension, hypertension were 5 people, while severe hypertension 1 people. There are differences / changes in blood pressure on workers aluminum before use and after use ear plug.